Do informal caregivers for elderly in the community use support measures? A qualitative study in five European countries. Issue 1 (December 2016) - Willemse, Evi; Anthierens, Sibyl; Farfan-Portet, Maria; Schmitz, Olivier; Macq, Jean; Bastiaens, Hilde; Dilles, Tinne; Remmen, Roy
Abstract Background Informal caregivers are essential figures for maintaining frail elderly at home. Providing informal care can affect the informal caregivers' physical and psychological health and labour market participation capabilities. They need support to prevent caregiver burden. A variety of existing support measures can help the caregiver care for the elderly at home, but with some limitations. The objective of this review was to explore the experiences of informal caregivers caring for elderly in the community with the use of supportive policy measures in Belgium and compare these to the experiences in other European countries. Methods An empirical qualitative case study research was conducted in five European countries (Belgium, The Netherlands, Luxembourg, France and Germany). Semi-structured interviews were conducted with informal caregivers and their dependent elderly. Interview data from the different cases were analysed. In particular data from Belgium was compared to data from the cases abroad. Results Formal services (e.g. home care) were reported to have the largest impact on allowing the caregiver to care for the dependent elderly at home. One of the key issues in Belgium is the lack of timely access to reliable information about formal and informal services in order to proactively support the informal caregiver. Compared to the other countries, informal caregivers in Belgium expressed more difficulties in accessing support measures and navigating through the health system. In the other countries information seemed to be given more timely when home care was provided via care packages. Conclusion To support the informal caregiver, who is the key person to support the frail elderly, fragmentation of information regarding supportive policy measures is an important issue of concern.